Rurality or distance to care and the risk of homelessness among Afghanistan and Iraq veterans. Issue 2 (5th June 2017) - Nelson, Richard E.; Gundlapalli, Adi; Carter, Marjorie; Brignone, Emily; Pettey, Warren; Byrne, Thomas H.; Montgomery, Ann Elizabeth; Rupper, Randall; Fargo, Jamison
Abstract : Purpose: Several risk factors have been identified in ongoing efforts by the US Department of Veterans Affairs (VA) to mitigate high rates of homelessness among veterans. To date, no studies have examined the relationship of rurality and distance to nearest VA facility to risk of homelessness. Due to challenges in accessing available services, the hypothesis was that rural-residing veterans are at greater risk for homelessness. The paper aims to discuss these issues. Design/methodology/approach: The cohort consisted of veterans who had separated from the military between 2001 and 2011. The authors used a forwarding address provided by the service member at the time of separation from the military to determine rurality of residence and distance to care. The authors examined differences in the rate of homelessness within a year of a veteran's first encounter with the VA following last military separation based on rurality and distance to the nearest VA facility using multivariable log-binomial regressions. Findings: In the cohort of 708, 318 veterans, 84.3 percent were determined to have a forwarding address in urban areas, 60.4 and 88.7 percent lived within 40 miles of the nearest VA medical center (VAMC), respectively. Veterans living in a rural area (RR=0.763; 95 percent CI=0.718-0.810) and those living between 20 and 40 miles (RR=0.893; 95 percent CI=0.846-0.943) and 40+ miles away from the nearest VAMC (RR=0.928; 95 percent CI=0.879-0.979) were at a lower risk for homelessness. Originality/value: The unique data set allowed the authors to explore the relationship between geography and homelessness. These results are important to VA and national policy makers in understanding the risk factors for homelessness among veterans and planning interventions.